"Click" Bis‐Triazoles as Neutral CH⋅⋅⋅Anion‐Acceptor Organocatalysts. Issue 5 (20th December 2012) - Beckendorf, Stephan; Asmus, Sören; Mück‐Lichtenfeld, Christian; García Mancheño, Olga
<x xml:space="preserve">Abstract</x> A new player on the field! "Click" bis‐triazoles have been introduced as a highly efficient new class of neutral CH⋅⋅⋅anion‐binding organocatalysts (see scheme). DFT and NMR studies were used to confirm this activation modus and identify the optimal catalyst.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>